М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
gjdhxhdbc
gjdhxhdbc
17.03.2020 17:21 •  Алгебра

1)-sqrt3-2sin3x< 0 2)ctg(pi/2+x)> sqrt3 п,с sqrt=корень

👇
Ответ:
Kate7779393727
Kate7779393727
17.03.2020

1).sqrt(3)*ctg(x)=-1 ctg(x)=-1/sqrt(3) x=arcctg(-1/sqrt(3))+pi*n x=2*pi/3+pi*n 2).cos(5x)=-1/2 5x=±arccos(-1/2)+2*pi*n 5x=±2*pi/3+2*pi*n x=±2*pi/10+2*pi*n/5 3).2sin(x/4-pi/3)+1=0 Sin(x/4)-pi/3)=-1/2 x/4-pi/3=(-1)^n*arcsin(-1/2)+pi*n x/4-pi/3=(-1)^n*7*pi/6+pi*n x/4=(-1)^n*7*pi/6+pi*n+pi/3 x=4*(-1)^n*7*pi/6+4*pi*n+4*pi/3 x=28*(-1)^n*pi/6+4*pi*n+4*pi/3 4).cos(9x)-cos(7x)+cos(3x)-cos(x)=0 (cos(9x)-cos(7x))+(cos(3x)-cos(x))=0 -2sin(8x)*sin(x)-2sin(2x)sin(x)=0 sin(x)(sin(8x-sin(2x))=0 sin(x)(2sin(3x)cos(5x)=0 sin(x)sin(3x)cos(5x)=0 a).sin(x)=0 => x=pi*n б).sin(3x)=0=> 3x=pi*n => x=pi*n/3 в).cos(5x)=0 => 5x=pi/2+pi*n => x=pi/10+pi*n/5 5).sin(2x)+2cos(2x)=1 sin(2x)+2cos(2x)=sin^2(2x)+cos^2(2x) cos(2x)=0 2x=pi/2+pi*n x=pi/4+pi*n/2 6).tg(x)-tg(3x)=0 sin(x)/cos(x)-sin(3x)/cos(3x)=0 sin(x)*cos(3x)- cos(x)*sin(3x)=0 sin(x-3x)=0 sin(-2x)=0 -2x=pi*n x=-pi*n/2 7).sin(11x)+((sqrt(3))/2)*sin(7x)+(1/2)*cos(7x)=0 sin(11x)+cos(pi/6)*sin(7x)+sin(pi/6)*cos(7x)=0 sin(11x)+sin(7x+pi/6)=0 2sin((11x+7x+pi/6)/2)*cos((11x-7x-pi/6)/2)=0 sin(9x+pi/12)*cos(2x-pi/12)=0 a).sin(9x+pi/12)=0 9x+pi/12=pi*n 9x=pi*n-pi/12 X=pi*n/9-pi/108 б).cos(2x-pi/12)=0 2x-pi/12=pi/2+pi*n 2x=pi/2+pi/12+pi*n 2x=7*pi/12+pi*n x=7*pi/24+pi*n/7

4,7(91 оценок)
Открыть все ответы
Ответ:
narenkovaa
narenkovaa
17.03.2020
1)12a²b³+3a³b²+16b²-a²=3a²b²(4b+a) + (4²b² - a²)=3a²b²(4b+a)+(4b-a)(4b+a)=
   
= (4b+a)(3a²b² + 4b- a)

2) 49c² -14c+1 -21ac+3a =  (49c²-14c+1) -3a(7c - 1) = (7c - 1)²  - 3a(7c - 1) =

=(7c-1)(7c - 1 - 3a)

3)ax²+ay²+x^4+2x²y²+y^4 = a(x²+y²)+(x^4+2x²y²+y^4) = a(x²+y²) +(x²+y²)²=

   = (x²+y²) (a +x²+y²)

4)  27c³-d³+9c²+3cd+d² = [(3c)³-d³]+ (9c²+3cd+d²) =

=[(3c - d)(9c²+3cd+d²)] + (9c²+3cd+d²) = (9c²+3cd+d²) (3c-d+1)

5) b³-2b²-2b+1 =(b³ + 1) - 2b( b+1) = (b+1)(b² -b+1) - 2b(b+1) =

  = (b+1)(b² -b+1-2b) = (b+1)(b² -3b+1)
4,5(32 оценок)
Ответ:
5473894
5473894
17.03.2020
1) а²-3а+2/а²-5а+6=(a-2)(a-1)/(a-3)(a-2)=a-1/a-3
а²-3а+2=0
D=9-8=1, D>0
a₁=3+1/2=2, a₂=3-1/2=1
a²-5a+6=0
D=25-24=1, D>0
a₃=5+1/2=3, a₄=5-1/2=2
ответ: а-1/а-3
2)5а²-9а-2/а²-3а+2=(a-2)(a+0,2)/(a-2)(a-1)=a+0,2/a-1
5а²-9а-2=0
D=81+40=121, D>0
a₁=9+11/10=2, a₂=9-11/10=-0,2
a²-3a+2=0
D=9-8=1, D>0
a₃=3+1/2=2, a₄=3-1/2=1
ответ: а+0,2/а-1
3) 6х²+х-2/3х²-4х-4=(х-1/2)(х+2/3)/(х-2)(х+2/3)=х-1/2/х-2
6х²+х-2=0
D=1+48=49, D>0
x₁=-1+7/12=1/2
x₂=-1-7/12=-8/12=-2/3
3x²-4x-4=0
D=16+48=64, D>0
x₃=4+8/6=2, x₄=4-8/6=-4/6=-2/3
ответ: х-1/2/х-2
4,6(65 оценок)
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ